Material, references, and sources for the Theoria entry on Wikipedia - Andersson, Niklas (University West, 2022)
Transcription interviews.

The dataset was originally published in DiVA and moved to SND in 2024.

Transkriptionsintervjuer.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Material, references, and sources for the Theoria entry on Wikipedia
Keywords: Theoria; Theoria; Entry; Entry; Wikipedia article; Wikipedia article; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning)